2012
DOI: 10.1261/rna.034520.112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic characterization of the 5′-triphosphate-dependent activation of PKR: Lack of 5′-end nucleobase specificity, evidence for a distinct triphosphate binding site, and a critical role for the dsRBD

Abstract: The protein kinase PKR is activated by RNA to phosphorylate eIF-2a, inhibiting translation initiation. Long dsRNA activates PKR via interactions with the dsRNA-binding domain (dsRBD). Weakly structured RNA also activates PKR and does so in a 59-triphosphate (ppp)-dependent fashion, however relatively little is known about this pathway. We used a mutant T7 RNA polymerase to incorporate all four triphosphate-containing nucleotides into the first position of a largely single-stranded RNA and found absence of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 43 publications
4
26
1
Order By: Relevance
“…Here, we find that both tails are required for activity and symmetric deletion to 10-nt 5 ′ and 3 ′ tails blocks activation. It has been reported that a 5 ′ -ppp is crucial for activation of PKR by the canonical ss-dsRNAs as well as ssRNAs containing short duplexes (Nallagatla et al 2007;Toroney et al 2012). In contrast, we find that this moiety does not significantly contribute to PKR activation and only slightly affects binding affinity.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Here, we find that both tails are required for activity and symmetric deletion to 10-nt 5 ′ and 3 ′ tails blocks activation. It has been reported that a 5 ′ -ppp is crucial for activation of PKR by the canonical ss-dsRNAs as well as ssRNAs containing short duplexes (Nallagatla et al 2007;Toroney et al 2012). In contrast, we find that this moiety does not significantly contribute to PKR activation and only slightly affects binding affinity.…”
Section: Discussioncontrasting
confidence: 70%
“…It has been reported that a 5 ′ -ppp is crucial for activation of PKR by the canonical ss-dsRNAs as well as ssRNAs containing short duplexes (Nallagatla et al 2007;Toroney et al 2012). However, dephosphorylation of ppp-15-15-15 and ppp-5-15-10 by treatment with calf intestinal alkaline phosphatase (CIP) has no significant effect on the extent of PKR activation (Fig.…”
Section: ′ -Triphosphatementioning
confidence: 99%
See 1 more Smart Citation
“…Possibly a 5′-triphosphate increases the binding affinity of some snoRNAs to PKR. Consistent with this hypothesis, PKR contains a potential triphosphate-binding site (31). Most snoRNAs are encoded in introns of host genes.…”
Section: Discussionmentioning
confidence: 69%
“…First, AAV vectors cannot be used in patients with preexisting antibodies 96 or lose their efficacy on development of such antibodies in treated patients. Second, even subtle structural differences between synthetic or recombinant small RNA molecules and endogenous counterparts, for example, miRs, may activate the innate immune system through both toll-like receptor-dependent and toll-like receptor-independent mechanisms, 97,98 and considerable efforts have been made to define structural requirements to avoid this problem. Only in noncardiovascular diseases, for example, cancer, immunostimulation by ncRNAs may be an acceptable or even useful side effect.…”
Section: Side Effectsmentioning
confidence: 99%